2009
DOI: 10.1002/ibd.20854
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil peptides 1–3 are useful biomarkers in patients with active ulcerative colitis

Abstract: HNP 1-3 is a novel biomarker that may be useful for diagnosing patients with active UC and predicting treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 34 publications
7
57
0
Order By: Relevance
“…Patients harboring PSD methylation could escape from severe inflammation because of insufficient host response to inflammation, such as neutrophil-induced apoptosis, leading to long-term, persistent inflammation without an appropriate host response. Our findings are congruent with those reported by Kanmura et al, who showed that the levels of neutrophil peptide were significantly higher in patients with active UC than in patients whose UC was in remission and tended to be higher than those in patients with colon cancer (46). UC-associated colorectal cancer progresses from areas of dysplastic mucosa (47,48) unlike sporadic colorectal cancer (49), which arises from adenomatous polyps.…”
Section: Discussionsupporting
confidence: 92%
“…Patients harboring PSD methylation could escape from severe inflammation because of insufficient host response to inflammation, such as neutrophil-induced apoptosis, leading to long-term, persistent inflammation without an appropriate host response. Our findings are congruent with those reported by Kanmura et al, who showed that the levels of neutrophil peptide were significantly higher in patients with active UC than in patients whose UC was in remission and tended to be higher than those in patients with colon cancer (46). UC-associated colorectal cancer progresses from areas of dysplastic mucosa (47,48) unlike sporadic colorectal cancer (49), which arises from adenomatous polyps.…”
Section: Discussionsupporting
confidence: 92%
“…Han et al [34] identified 16 additional proteins that were expressed differently between active and inactive CD. Kanmura et al [23] asso ciated a higher level of HNP 13 with a positive response following induction of corticosteroid therapy, whilst non responders had lower HNP 13 levels. Meuwis et al [37] published a second report which identified a serum protein profile which correlated with infliximab response.…”
Section: Pre-clinical Presentationmentioning
confidence: 99%
“…From the protein spectra detected, platelet factor 4, myeloid related protein 8, fibrinopeptide A and haptoglobin α2 were considered diagnostically important. Kanmura et al [23] examined UC serum samples using SELDITOF MS and identified that human neutrophil peptide (HNP) 13 was differenti ally expressed. HNP 13 was confirmed by ELISA to differentiate active UC from inactive UC, all CD cases and controls, but not colorectal cancer.…”
Section: Biomarker Discovery Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that plasma concentrations of HNP 1-3 in patients with active UC were significantly higher than those in healthy subjects or patients with inactive UC, CD, or infectious enterocolitis, which may reflect the infiltration and activation of neutrophils in the intestinal mucosa of patients with active UC. Thus, HNP 1-3 are novel biomarkers for assessing UC disease activity and therapeutic response [11] . However, there are no data on HNP 1-3 levels in the stools of patients with IBD, and whether HNP 1-3 are candidate fecal markers of intestinal inflammation.…”
mentioning
confidence: 99%